Nano-magnetism unleashed: Targeted healing in yoga and physiotherapy with magnetic nanoparticles - Zulfiqar, Noor; Asif, Maryam; Tayyab, Hafiz Salman; Shaukat, Misbah; Mehmood, Humna; Inam, Fawad (Nano and Medical Materials, 2024)
This review article explores the innovative applications of magnetic nanoparticles (MNPs) in yoga and physiotherapy for targeted healing. MNPs’ unique magnetic properties enable precise treatment and minimal invasiveness, offering significant potential in medical applications. Recent studies highlight the promising integration of MNPs into yoga and physiotherapy, enhancing the efficacy of these interventions by precisely targeting affected areas. This review also examines nanotechnology’s pivotal role in modern medical practices, showcasing MNPs’ contributions to pain management and tissue regeneration. By analyzing current developments and future prospects, the article aims to inspire further research and innovation in MNP-based targeted healing within yoga and physiotherapy.